Community Empowerment through Optimization of Geographic Indication (A Study on Local Products in Tambakroto Village, Sayung District, Demak Regency ) - Prabowo, M Shidqon (Faculty of Law, Universitas Negeri Semarang, 2019)
Geographical Indication is a sign used on goods that have a specific geographical origin and has the quality or reputation is based on place of origin. In general, Geographical Indications is the name of the place of origin of such goods. Agricultural products typically have qualities that are formed from the place of production and are influenced by local factors are specific, such as climate and soil. Sub Tambakroto Sayung is one of the District in the city of Demak, which has the potential to geographical indications. The potential of geographical indications which are owned by the city of Demak District Tanbakroto Sayung have the geographic conditions, natural resources, agricultural products, crops and cultural traditions. The problem in this research are: 1). Potential geographical indication of what is owned by the District of Demak TambakrotoSayung? 2). What policies adopted to improve the welfare of society through excellence geographical indications in the District of Demak Tambakroto Sayung? This study aims to: 1). Register geographical indications advantages possessed by Tambakroto Sayung District of Demak, 2). Knowing the supporting and inhibiting factors in empowering excellence Tambakroto Sayung geographical indications in the District of Demak, 3). Produce a model of community empowerment based on the superiority of geographical indications in the DistrictTambakroto Demak.This research was carried out by empirical methods juridical approach. The specifications used in this research is descriptive analysis. The location of this research is in DistrictTambakroto sayung Demak. The research data collected by way of interviews, documentation and direct observations in the field.The results of this study is the potential for geographical indications which are owned by the District Sayung the fruit tempe and lontong fruit. Sub Tambakroto Sayung has advantages over other regions in wilyah city of Demak. Excellence is the product of geographical indication in the form of fruit tempe and lontong fruit known by the name of the tempe and lontong tambakroto. Potential is the potential for geographical indications that have long existed in the district since Tambakroto But this time the potential was nearly extinct where the biggest factor is masyarat nor the relevant local government is not keeping well and not doing it continuously for the potential development of geographical indication. Development and empowerment are preferred to be done in maintaining the geographical indication products Tambakroto District. After that application was made for the protection of geographical indication products. Steps are still far to be done but it is not impossible to do. District policy has not led to concrete Tambakrotoin pengupayaaan, empowerment and development of products of geographical indication Tambakroto District. Initial thing to do is perform on the public understanding of the meaning of Sub Tambakroto importance of geographical indication of products that have been owned by the community such Tambakroto District. Geographical indication of products that have been developed and empowered as optimal as possible will support the welfare of the people own Tambakroto District. Keywords: Community Empowerment, Geographical Indications.